A global core outcome measurement set for snakebite clinical trials - Abouyannis, Michael (2023)
Snakebite clinical trials have often used heterogeneous outcome measures and there is an urgent need for standardisation. A globally representative group of key stakeholders came together to reach consensus on a globally relevant set of core outcome measurements. Outcome domains and outcome measurement instruments were identified through searching the literature and a systematic review of snakebite clinical trials. Outcome domains were shortlisted by use of a questionnaire and consensus was reached among stakeholders and the patient group through facilitated discussions and voting. Five universal core outcome measures should be included in all future snakebite clinical trials—mortality, WHO disability assessment scale, patient-specific functional scale, acute allergic reaction by Brown criteria, and serum sickness by formal criteria. Additional syndrome-specific core outcome measures should be used depending on the biting species. This core outcome measurement set provides global standardisation, supports the priorities of patients and clinicians, enables meta-analysis, and is appropriate for use in low-income and middle-income settings.